Assessment of the determinants that influence the adoption of sustainable soil and water conservation practices in Techiman Municipality of Ghana - Darkwah, K.A.; Kwawu, J.D.; Agyire-Tettey, F.; Sarpong, D.B. (International Soil and Water Conservation Research, 2019)
This paper assesses the relationship between farmer characteristics and the degree to which nine soil and water conservation practices (SWCPs) are adopted by 300 maize farmers in Techiman Municipality, Ghana. Farmers were surveyed for their adoption of nine SWCPs, and 24 other characteristics including demographics, socio-economic factors, risk factors and costs of production. Sustainable soil and water conservation practices (SWCPs) in sub-Saharan Africa such as Ghana are important because they have positive effects on yield, increase sustainability of farming, stop degradation and reduce soil erosion. The adoption of sustainable soil and water conservation practices in the agricultural industry of Ghana has been variable. This study aims to explain differences in farmer adoption of SWCPs, by assessing factors that vary with the number of different SWCPs used by farmers. Hence, the Poisson model was used. The results show that farmer's household size, farm size, access to credit services and formal training of maize farmer have a positive significant association with the number of soil and water conservation practices adopted by maize farmers while distance to nearest output market, distance to input center, access to extension services, and risk of pest and diseases have a negative significant association with the number of soil and water conservation practices adopted by maize farmers at 5% significance level. The study concludes that any further research in Techiman Municipality on soil and water conservation practices should acknowledge the mixture of personal and demographic, institutional, socio-economic and risk factors. This suggests that agricultural policies formulated by the government should be aimed at supporting maize farmers to have access to extension service contact for frequent disseminating of agricultural technology information which is likely to increase the rate of adoption of soil and water conservation practices. © 2019 International Research and Training Center on Erosion and Sedimentation and China Water and Power Press
Keywords: Adoption; Correlation; Poisson regression; Sustainable soil and water conservation practices